The Influence of Hearing Impairment on Driving Avoidance Among a Large Cohort of Older Drivers. (December 2021) - Vivoda, Jonathon M.; Molnar, Lisa J.; Eby, David W.; Bogard, Scott; Zakrajsek, Jennifer S.; Kostyniuk, Lidia P.; St. Louis, Renée M.; Zanier, Nicole; LeBlanc, David; Smith, Jacqui; Yung, Raymond; Nyquist, Linda; et al.
As people age, some of the commonly experienced psychomotor, visual, and cognitive declines can interfere with the ability to safely drive, often leading to situational avoidance of challenging driving situations. The effect of hearing impairment on these avoidance behaviors has not been comprehensively studied. Data from the American Automobile Association (AAA) Longitudinal Research on Aging Drivers (LongROAD) study were used to assess the effect of hearing impairment on driving avoidance, using three measures of hearing. Results indicated that hearing loss plays a complex role in driving avoidance, and that an objective hearing measure was a stronger predictor than hearing aid use and self-rated hearing. Greater hearing impairment was related to less nighttime and freeway driving, more trips farther than 15 mi from home, and lower odds of avoiding peak driving times. The moderating influence of hearing on both vision and cognition is also discussed, along with study implications and future research.